Saddle-node bifurcations in power systems - Cañizares Esguerra, Claudio Adrián (1993)
Saddle-node bifurcations are dynamic instabilities of differential equation models that have been associated to voltage collapse problems in power systems. This paper presents the conditions needed for detecting these type of bifurcations in a dynamic model of ac/dc systems, represented by differential equations. It is also shown that two methods typically used to detect saddle-node bifurcations, namely, direct and parameterized continuation methods, are numerically robust at the bifurcation point, wich makes them ideal for computer implementation.